The Research Center for Science and Culture, Angasolka settlement, Baikal - Zapova, Elizaveta; Druzhinina, Inna (project baikal, 2021)
The construction of the future center for science and culture is related to the necessity of scientific research and reclamation of the central ecological area of Baikal. Its functions are research, site improvements and tourism compatible with present-day accessibility and environmental safety requirements. The reclamation of the granite and ballast quarry and the introduction of research, cultural-educational and tourist functions will provide solutions to many ecological and economic problems of the area.